РОЛЬ ИННОВАЦИЙ И ИННОВАЦИОННОГО ПРОЦЕССА В РАЗВИТИИ ПИЩЕВОЙ ПРОМЫШЛЕННОСТИ (International Journal of Innovative Technologies in Economy, 2018)
The author concludes that the development of the food industry is possible to provide due to innovations and management of the innovation process. The author classifies and gives concepts to innovations in the food industry. The article highlights the factors that limit the development of the food industry. The SWOT analysis of the food industry position is presented. The main problems in the food industry are revealed. The author proposes a number of measures for the development of the food industry. The prospects of development of innovative component of the food industry and measures for management of innovative process in the food industry are offered.